2015
DOI: 10.1039/c5ce00901d
|View full text |Cite
|
Sign up to set email alerts
|

Selective gelation of N-(4-pyridyl)nicotinamide by copper(ii) salts

Abstract: ARTICLE This journal isWe report the selective gelation properties of copper(II) complexes of N-(4pyridyl)nicotinamide (4PNA). The morphology of the xerogels was examined by scanning electron microscopy (SEM). Correlation of X-ray powder diffraction (XRPD) pattern of the xerogels and single crystal structure of copper(II) acetate complex suggests that the single crystal X-ray data represents a good structural model for the gel fibers themselves and that gelation arises from the presence of a 1D hydrogen bonded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…We have been successful in identifying the role of various nonbonding interactions in gel formation by comparing the molecular assembly in crystalline and gel/dried gel states [ 30 , 43 , 44 , 45 ]. Although, the xerogel does not represent the exact structure of the gel state since the drying process can lead to a morphological change or phase transition [ 46 ], this approach is still recognized as the most useful strategy to unravel the self-assembly of a gelator [ 3 , 7 , 29 , 30 , 43 , 44 , 45 ]. The self-assembly of L 1 and L 2 in the gel state was correlated with respective crystal structures by comparing the powder X-ray pattern of the bulk crystals and dried gels with the crystal structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have been successful in identifying the role of various nonbonding interactions in gel formation by comparing the molecular assembly in crystalline and gel/dried gel states [ 30 , 43 , 44 , 45 ]. Although, the xerogel does not represent the exact structure of the gel state since the drying process can lead to a morphological change or phase transition [ 46 ], this approach is still recognized as the most useful strategy to unravel the self-assembly of a gelator [ 3 , 7 , 29 , 30 , 43 , 44 , 45 ]. The self-assembly of L 1 and L 2 in the gel state was correlated with respective crystal structures by comparing the powder X-ray pattern of the bulk crystals and dried gels with the crystal structure.…”
Section: Resultsmentioning
confidence: 99%
“…The amide/urea functionalized LMWGs can be considered as classical stimuli-responsive soft materials due to their response to an external stimulus such as light, redox, pH, and salts/ions [ 29 , 37 , 43 , 47 ]. We have shown that the anion responsive properties of supramolecular gels can be used to detect cyanide anions in water by monitoring the gel to sol transition [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…394 In some cases, aging can causes a considerable weakening of interlocked fibre networks leading to spontaneous evolution to crystallization. [395][396][397][398][399][400][401] Furthermore, there are examples where the aged gel shows a shrinking behavior. [402][403][404] Recently, Sugiura et al constructed a hydrogel system involving hydrazone-oxime exchange reaction in response to hydroxylamine (Fig.…”
Section: Time Programmable Self-regulating Gel To Gel Transitionsmentioning
confidence: 99%
“…Both supramolecular gelation and crystallization are non-equilibrium self-assembly processes that occur under supersaturated conditions and are characterized by a nucleation and growth phase [ 102 , 103 ]. For this reason, many experimental studies on supramolecular gels report powder X-ray diffraction data of the dried xerogel with the aim of extracting useful information on the structure of the gel network [ 5 , 104 , 105 ]. From the 1960s onwards, crystal structure prediction (CSP) has become a field on its own and has experienced an enormous development of applicable techniques able to predict the crystal morphology based on the molecular structure [ 106 , 107 , 108 , 109 , 110 ].…”
Section: Predicting Supramolecular Gelationmentioning
confidence: 99%